A Cost Reimbursement Model for Hepatitis C Treatment Care Coordination. Issue 3 (May 2019) - Behrends, Czarina N.; Eggman, Ashley A.; Gutkind, Sarah; Bresnahan, Marie P.; Fluegge, Kyle; Laraque, Fabienne; Litwin, Alain H.; Meissner, Paul; Shukla, Shuchin J.; Perumalswami, Ponni V.; Weiss, Jeffrey; Wyatt, Brooke E.; et al.
Abstract : Objective: To estimate the cost of delivering a hepatitis C virus care coordination program at 2 New York City health care provider organizations and describe a potential payment model for these currently nonreimbursed services. Design: An economic evaluation of a hepatitis C care coordination program was conducted using micro-costing methods compared with macro-costing methods. A potential payment model was calculated for 3 phases: enrollment to treatment initiation, treatment initiation to treatment completion, and a bonus payment for laboratory evidence of successful treatment outcome (sustained viral response). Setting: Two New York City health care provider organizations. Participants: Care coordinators and peer educators delivering care coordination services were interviewed about time spent on service provision. De-identified individual-level data on study participant utilization of services were also used. Intervention: Project INSPIRE is an innovative hepatitis C care coordination program developed by the New York City Department of Health and Mental Hygiene. Main Outcome Measures: Average cost per participant per episode of care for 2 provider organizations and a proposed payment model. Results: The average cost per participant at 1 provider organization was 787 (522 nonoverhead cost, 264 overhead) per episode of care (5.6 months) and 656 (429 nonoverhead cost, 227 overhead, 5.7 months) at the other one. The first organization had a lower macro-costing estimate (561 vs 787) whereas the other one had a higher macro-costing estimate (775 vs 656). In the 3-phased payment model, phase 1 reimbursement would vary between the provider organizations from approximately 280 to 400, but reimbursement for both organizations would be approximately 220 for phase 2 and approximately 185 for phase 3. Conclusions: The cost of this 5.6-month care coordination intervention was less than 800 including overhead or less than 95 per month. A 3-phase payment model is proposed and requires further evaluation for implementation feasibility. Project INSPIRE's HCV care coordination program provides good value for a cost of less than 95 per participant per month. The payment model provides an incentive for successful cure of hepatitis C with a bonus payment; using the bonus payment to support HCV tele-mentoring expands HCV treatment capacity and empowers more primary care providers to treat their own patients with HCV. Abstract : Supplemental Digital Content is Available in the Text.